The Importance of Treasury and Central Bankbills in the Implementation of Monetary Policy - Mansur Alisherovich, Mansurov (International Journal of Psychosocial Rehabilitation, 2020)
This study explores the problem of using Treasury Bills and central bank bills as a means of monetary policy by countries at the level of development and the simultaneous use of two types of securities. It is noteworthy that in developed countries, there are treasury bills or central bank bills, and in developing countries, both bills are used. Also, in the developed world, there is more use of Treasury bills than central bank bills. The employment of two types of securities leads to the segmentation of the bond market, the deterioration of the central bank's revenues and the growth of public debt. Based on the problems arising from the simultaneous use of two different bills, it was proposed to include the central bank bills in Treasury bills in countries with two different bills.